2017
DOI: 10.1007/s11103-017-0670-0
|View full text |Cite
|
Sign up to set email alerts
|

ptxD gene in combination with phosphite serves as a highly effective selection system to generate transgenic cotton (Gossypium hirsutum L.)

Abstract: This report demonstrates the usefulness of ptxD/phosphite as a selection system that not only provides a highly efficient and simple means to generate transgenic cotton plants, but also helps address many of the concerns related to the use of antibiotic and herbicide resistance genes in the production of transgenic crops. Two of the most popular dominant selectable marker systems for plant transformation are based on either antibiotic or herbicide resistance genes. Due to concerns regarding their safety and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Indeed, the global advance promulgating engineered crops is pillared on today's artificial intelligence-guided plant codon optimization rules offered by both large and small boutique DNA houses. However, there has been success expressing native bacterial sequences in plants, i.e., in the case of cotton expressing the native sequence of the P. stutzeri gene ptxd (PHOSPHONATE DEHYDROGENASE) [127,128]. One can dare to fathom how a universally-functional nosZ expression system could conceivably redirect some aspects of GHG mitigation research.…”
Section: Novel Breeding Task: "Gas Cracking" Plantsmentioning
confidence: 99%
“…Indeed, the global advance promulgating engineered crops is pillared on today's artificial intelligence-guided plant codon optimization rules offered by both large and small boutique DNA houses. However, there has been success expressing native bacterial sequences in plants, i.e., in the case of cotton expressing the native sequence of the P. stutzeri gene ptxd (PHOSPHONATE DEHYDROGENASE) [127,128]. One can dare to fathom how a universally-functional nosZ expression system could conceivably redirect some aspects of GHG mitigation research.…”
Section: Novel Breeding Task: "Gas Cracking" Plantsmentioning
confidence: 99%
“…Furthermore, the use of metabolic markers helps address the regulatory and safety concerns associated with the environmental spread of antibiotic resistance genes by horizontal gene transfer (HGT) during commercial cultivation (EFSA GMO Panel 2004;Beacham et al 2017). Various reports have shown that ptxD can serve as an efficient marker for generation of transgenic plants (López-Arredondo and Herrera-Estrella 2013; Nahampun et al 2016;Pandeya et al 2017), yeasts (Kanda et al 2014) and cyanobacteria (Selão et al 2019). However, whilst the very low abundance of Phi in the natural environment means that HGT of the ptxD marker to other microbial species is unlikely to confer any selective advantage, this could still compromise its use as for crop protection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of ecologically rare or xenobiotic sources of macronutrients has been explored as a means to generate selective pressure towards the growth of genetically modified organisms without the use of antibiotics (Kanda et al, 2014;Loera-Quezada et al, 2016;Pandeya et al, 2017;Polyviou et al, 2015;Shaw et al, 2016) as well as to allow genetically modified plants to outcompete weeds, while consuming considerably less phosphorus (Lopez-Arredondo and Herrera-Estrella, 2012). To this end, phosphite dehydrogenase (PtxD), an enzyme converting phosphite, an ecologically rare form of phosphorus, into phosphate, has been introduced into a variety of organisms, and in some cases used as a selectable marker (Kanda et al, 2014;Lopez-Arredondo and Herrera-Estrella, 2012;Nahampun et al, 2016;Pandeya et al, 2017). A synthetic pathway to utilize melamine, a xenobiotic nitrogen-rich compound, has also been devised and introduced into different organisms (Shaw et al, 2016).…”
Section: Introductionmentioning
confidence: 99%